(untitled) (Journal of Asian Development Studies, 2025)
Flash floods have become an increasing menace to mountainous communitises, particularly in the Hindu-Kush–Himalayan region, where climate change has intensified extreme precipitation and glacial melt. This paper examines the 2022 flash flood event in Punial valley, District Ghizer, northern Pakistan, within the broader context of climate-induced disasters in alpine environments. The primary objective is to evaluate the underlying causes, Impacts, dynamics, socio-economic consequences of 2022 flash floods on local livelihoods and infrastructure. A mix-methods approached was employed, combining quantitative data from a structured household survey (n=212) with qualitative insights from focus group discussions & key informant interviews. Results indicate that the principal drivers of 2022 were unprecedented monsoon rainfall, accelerated snow and glacial melt due to elevated temperatures, and the regions complex topography. These factors collectively caused extensive destruction of housing, roads, bridges, irrigation systems, and agriculture land severely disrupting livelihoods and exacerbating pre-existing vulnerabilities among marginalized groups, including landless farmers and women-headed households. The study further evaluates local and institutional response capacities, identifying critical gaps in early warning systems, evacuation planning and post-disaster shelter provision. Findings underscore an urgent need for community-based disaster risk reduction, improved early warning mechanisms, climate resilient infrastructure, and sustainable land-use planning to enhance adaptive capacity in Gilgit-Baltistan. The paper also integrates lessons from the 2022 & 2025 flood events, offering actionable recommendation aligned with Pakistan National Adaptation Plan. This research contributes to the growing literature on flash flood vulnerability and resilience in high-altitude regions and provides evidence- based guidance for policy makers and disaster management practitioners.